Penerapan Teknik Non-Linear Editing dalam Pembuatan Video Feature “Berani Melangkah Menuju Sejahtera” - Sabatini, Sabila; Agustin, Herlina; Dewi, Retasari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Video editor play an important role in building the storyline and visual quality of audiovisual productions. In the production of the Feature video “Berani Melangkah Menuju Sejahtera”, the editor applied non-linear Editing (NLE) techniques throughout the process. The purpose of this paper is to explain the application of NLE techniques, which include the processes of logging, offline Editing, online Editing, and rendering. The creation process consists of three main stages: pre-production, production, and post-production, with a primary focus on the post-production stage. The primary focus of the analysis is on the post-production phase, where non-linear Editing techniques are applied comprehensively. The Editing process is outlined through the stages of logging for efficient footage management, offline Editing to build the initial narrative structure, online Editing for precise visual and audio refinement, and rendering for finalizing the work. The use of NLE allows for high flexibility in exploring various cut options, complex visual and audio synchronization, and the integration of graphic elements to support the storyline. The results of the analysis showed that the author was able to enhance narrative quality and visual aesthetics through the structured application of NLE techniques. This work not only conveys a social message but also creates a viewing experience, enabling the message to be persuasively received by the audience.